TEACHER’S EFFORT TO ENRICH STUDENTS’ VOCABULARY IN TEACHING ENGLISH AT SECOND GRADE OF ISLAMIC JUNIOR HIGH SCHOOL ASAS ISLAMIYAH JAMBI - Rahmah, Rahmah; Astika, Yulia Wiji (LPPM Universitasdiwangsa Jambi, 2020)
Language is the basic skills are needed for real communication among people. By using language, we will able to express our ideas and feeling. In Indonesia, English language is learned by students as a foreign language. As know, English vocabulary has become an important part in the teaching-learning process in the classroom. It is based on source to learn English therefore we must have good English and enough vocabulary. Without that we will not be able to use English better in our life and we can’t master English conversation with other people. The researcher interests to appoint this problem by title: Teacher’s Effort to Enrich Students’ Vocabulary in Teaching English at Second Grade of Asas Islamiyah Jambi. The method had used in this research was qualitative. The population in this research are the students of Asas Islamiyah Jambi. The samples were 30 students of the second grade. In this research, the instrument used to collected the data are observation, interview with English teachers and documentation. The results of the research are the application of teaching vocabulary by using word category method can be achieved by some students in second grade at Islamic Junior High School Asas Islamiyah Jambi. The teaching vocabulary by using word category at Islamic Junior High School Asas Islamiyah Jambi can make the students fun ad active and also make the students to be able to remember the vocabulary easily.